When You Become a Superman: Subliminal Exposure to Death-Related Stimuli Enhances Men’s Physical Force - Kawakami, Naoaki; Miura, Emi; Nagai, Masayoshi (Frontiers in Psychology, 2018)
Research based on terror management theory (TMT) has consistently found that reminders to individuals about their mortality engender responses aimed at shoring up faith in their cultural belief system. Previous studies have focused on the critical role that the accessibility of death-related thought plays in these effects. Moreover, it has been shown that these effects occur even when death-related stimuli are presented without awareness, suggesting the unconscious effects of mortality salience. Because one pervasive cultural ideal for men is to be strong, we hypothesized that priming death-related stimuli would lead to increasing physical force for men, but not for women. Building on self-escape mechanisms from TMT, we propose that the mechanism that turns priming of death-related stimuli into physical exertion relies on the co-activation of the self with death-related concepts. To test this hypothesis, we subjected 123 participants to a priming task that enabled us to combine the subliminal priming of death-related words with briefly presented self-related words. Accordingly, three different conditions were created: a (control) condition in which only self-related stimuli were presented, a (priming) condition in which death-related words were subliminally primed but not directly paired with self-related stimuli, and a (priming-plus-self) condition in which death-related words were subliminally primed and immediately linked to self-related stimuli. We recorded handgrip force before and after the manipulations. Results showed that male participants in the priming-plus-self condition had a higher peak force output than the priming and control conditions, while this effect was absent among female participants. These results support the hypothesis that unconscious mortality salience, which is accompanied with self-related stimuli, increases physical force for men but not for women. The gender difference may reflect the cultural belief system, in which individuals are taught that men should be strong. Thus, the unconscious mortality salience produced by exposure to the death-related stimuli motivates need to conform to this internalized cultural standard.